Interpositional arthroplasty with temporalis myofascial flap reconstruction in a case of temporomandibular joint bony ankylosis: a case report and review of literature - Vishwani, Ankit; Arora, Vipin; Goyal, Kavita; Arya, Suvercha; Khan, Mohsin (International Surgery Journal, 2019)
The report describes the treatment of a 30 year old female patient having unilateral right temporomandibular joint (TMJ) bony ankylosis whose mouth opening was restricted to 5 mm and had additional mandibular retrognathism causing severe mastication problems besides speech difficulties and low morale. The ankylosis had resulted in facial asymmetry due to bony hard swelling in front of right tragus. The patient was taken up for right interpositional arthroplasty with temporalis myofascial flap reconstruction by pre auricular approach and left coronoidectomy by intraoral approach as a preferred technique. A satisfactory mouth opening of 33 mm was achieved in immediate post-operative. Patient was followed up with aggressive mouth opening exercises in postoperative period.